Administrative Structure and Inner-Metropolitan Tax Competition - Björn Kauder (Verein für Socialpolitik, 2010)
This paper considers the impacts of differently formed borders of municipalities on local business tax policy. First a model is presented that shows the dependence of the level of taxation on the administrative structure. Afterwards, data from Germany are employed to discover the effects of the number and size of municipalities within agglomerations. The results show that the administrative structure matters for the level of local business taxation. On the one hand, the core cities tax rate in a monocentric region is the lower, the more municipalities are situated within a certain distance from the city. This effect is the more important, the smaller the region that is considered. On the other hand, the tax of the core city is the higher, the larger its share in the agglomeration. Thereby, the result has more power for larger regions. The empirical results coincide with the results from tax competition theory.
Keywords: H25; H71; H73; 330; Local Business Taxation; Municipal Borders